2017
DOI: 10.1614/wt-d-16-00061.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage Method on Management ofAmaranthusSpecies in Soybean

Abstract: A field study was conducted in 2014 and 2015 in Arkansas, Illinois, Indiana, Ohio, Tennessee, Wisconsin, and Missouri to determine the effects of tillage system and herbicide program on season-long emergence of Amaranthus species in glufosinate-resistant soybean. The tillage systems evaluated were deep tillage (fall moldboard plow followed by (fb) one pass with a field cultivator in the spring), conventional tillage (fall chisel plow fb one pass with a field cultivator in the spring), minimum tillage (one pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Shifting from CT to conservation tillage can influence weed population dynamics by altering the vertical distribution of weed seeds in soil and impacting weed seedbank persistence and seedling recruitment (Farmer et al 2017;Young and Thorne 2004). The lack of soil inversion in conservation-tillage systems may lead to the accumulation of weed seeds in the topsoil layer, thus altering their distribution in the soil profile.…”
Section: Introductionmentioning
confidence: 99%
“…Shifting from CT to conservation tillage can influence weed population dynamics by altering the vertical distribution of weed seeds in soil and impacting weed seedbank persistence and seedling recruitment (Farmer et al 2017;Young and Thorne 2004). The lack of soil inversion in conservation-tillage systems may lead to the accumulation of weed seeds in the topsoil layer, thus altering their distribution in the soil profile.…”
Section: Introductionmentioning
confidence: 99%
“…Tillage is an important aspect of farm management. Non-inversion or minimum tillage reduces energy usage, enables faster soil preparation and improves soil aggregation (Vakali et al, 2011;Bottineli et al, 2017), but deep-tillage implements that invert soil layers, bury weed seeds deep enough to prevent their germination and emergence (Farmer et al, 2017). In some cases, integrated use of mouldboard plough reduced the emergence of weeds by at least 95% over two growing seasons (Bagavathiannan, Norsworthy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Clements et al (1996) reported that more than 70% of the total weed seeds were observed near the soil surface in the NT system compared to only 37% of seeds in the CT system. Farmer et al (2017) also reported that 91% of seeds of Amaranthus species were located in the 0-to 5-cm depth in the NT system compared to 71% in the CT system. The occurrence of seeds beyond 15-cm depth in NT could be likely due to movement of seeds through soil cracks and short distance movement of seed through ingestion and excretion by earthworms (Hurka & Haase, 1982).…”
Section: Seedbank Distributionmentioning
confidence: 93%
“…Steckel et al (2007) observed that the density of waterhemp (Amaranthus rudis Sauer), a small-seeded broadleaf weed, was more (3,940 plants m -2 ) in the NT system compared to a field under chisel plowing (2,100 plants m -2 ). Likewise, Farmer et al (2017) reported 28% greater Palmer amaranth (A. palmeri S. Watson) density in NT than in CT systems.…”
Section: Introductionmentioning
confidence: 93%